PSYCHOMETRIC VALIDATION OF THE BAHASA MALAYSIA VERSION OF THE EORTC QLQ-C30 IN MALAYSIAN COLORECTAL CANCER PATIENTS - Bello Arkilla Magaji; Foong Ming Moy; Chee Wei Law; Ismail Sagap; April Camilla Roslani (Malaysian Journal of Public Health Medicine, 2020)
This study aimed to assess the validity and reliability of the Bahasa Malaysia (BM) version of European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire core (QLQ-C30) (version 3.0) in Malaysian patients with colorectal cancer. A cross sectional study design was used to obtain data from patients receiving treatment at two teaching hospitals in Kuala Lumpur, Malaysia. Self-administered method was used. Statistical analysis included reliability, convergent and discriminant validity and known-groups comparisons. Statistical significance was based on p value ? 0.05. The internal consistency Cronbach’s alpha coefficient (?) was acceptable (> 0.70) in all scales but cognitive (? = 0.56) and pain in patients with stoma bag (? = 0.35). Test-retest coefficients were high (r = 0.93 to 1.00). All items showed adequate convergent validity (r > 0.40) except for questionnaire item 5 “needs help in eating/dressing/washing”. Similarly, criteria for discriminant validity were achieved in all but item 10 “need rest”. Patients with high Karnofsky Performance Scores (KPS) scores reported significantly less dyspnoea (p = 0.021) and appetite loss (p = 0.047) compared to patients with low KPS scores. There was no significant difference between patients with and without stomas. The psychometric properties of the BM version of the QLQ-C30 were comparable to previous studies in other settings. Therefore, the questionnaire could be used to measure quality of life in Malaysian patients with colorectal cancer.